(untitled) (Journal of Atomic and Molecular Sciences, 2016)
We theoretically study the high-order harmonic and the isolated attosecond pulse generation in the near-infrared (IR) (3-fs, 800 nm) laser pulse by adding a terahertz (THz) controlling field with proper phases. It is found that the high-order harmonic spectrum in the IR pulse by adding a terahertz field is broader and smoother than that in the single IR pulse. The underlying physical mechanism is illustrated by means of the time-frequency analysis and the three-step model. We calculate the ionization rate by ADK model to further demonstrate the process of high-order harmonic generation. By superposing a proper range of harmonic spectrum, an isolated attosecond pulse with the duration of 71 as is obtained.